2005
DOI: 10.1073/pnas.0409861102
|View full text |Cite
|
Sign up to set email alerts
|

RNA interference rescue by bacterial artificial chromosome transgenesis in mammalian tissue culture cells

Abstract: RNA interference (RNAi) is a widely used method for analysis of gene function in tissue culture cells. However, to date there has been no reliable method for testing the specificity of any particular RNAi experiment. The ideal experiment is to rescue the phenotype by expression of the target gene in a form refractory to RNAi. The transgene should be expressed at physiological levels and with its different splice variants. Here, we demonstrate that expression of murine bacterial artificial chromosomes in human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 41 publications
2
78
0
Order By: Relevance
“…The latter approaches readily generate targeted genomic deletions, which cause full gene inactivation by non-homologous endjoining rather than a knockdown achieved by shRNA, but the introduction of specific mutations via homologous recombination is substantially less efficient, and requires expensive and timeconsuming screening for correct clones. Moreover, the system is not reversible, and rescue experiments require transfection of the cells with plasmid or bacmid vectors followed by clonal selection 12,13 , which could introduce artifacts. Our system controls for off-target effects of the shRNA by including a control that expresses the tagged WT variant in the presence of the shRNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter approaches readily generate targeted genomic deletions, which cause full gene inactivation by non-homologous endjoining rather than a knockdown achieved by shRNA, but the introduction of specific mutations via homologous recombination is substantially less efficient, and requires expensive and timeconsuming screening for correct clones. Moreover, the system is not reversible, and rescue experiments require transfection of the cells with plasmid or bacmid vectors followed by clonal selection 12,13 , which could introduce artifacts. Our system controls for off-target effects of the shRNA by including a control that expresses the tagged WT variant in the presence of the shRNA.…”
Section: Discussionmentioning
confidence: 99%
“…An important shortcoming of RNAi technology are off-target effects 11 ; however, specificity can be demonstrated by rescue of the observed phenotype through expression of an RNAi-resistant mRNA 12,13 . Originally designed as a control experiment to check the specificity of RNAis, this approach has been extended to deploy RNAi-resistant mRNAs to express protein variants.…”
mentioning
confidence: 99%
“…In mammalian cells, the lack of efficient homologous recombination makes the functionality test difficult. Kittler et al 16 demonstrated that expression of murine bacterial artificial chromosomes (BAC) in human cells provides a reliable method to create RNA interference (RNAi)-resistant tagged transgenes. In such cells, the endogenous human gene can be knocked down by RNAi, while the corresponding murine gene expressed from the integrated BAC resists the RNAi treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of XGrb2 SiL did not result in acute upregulation of endogenous Grb2 mRNA due to transfection artifacts, demonstrating that endogenous Grb2 silencing can be rescued at the protein level. Our laboratory has previously shown that Grb2, as part of a Shc-Grb2-SOS complex is essential for the signaling of the phospholipase D2 (PLD2) isoform through the SOS-RAS-RAF-MAPKK-MAPK signaling cascade and eventual effect on DNA synthesis and cell growth [12,13]. Efficient signaling requires association of the lipase with Grb2 through an identified residue, (as the Src homology 'SH' region-2 binds to phosphorylated tyrosine residues).…”
Section: Discussionmentioning
confidence: 99%